2010
DOI: 10.1159/000319006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Intracranial Complications after Pediatric Traumatic Head Injury: An Observational Study of Children Submitted to a Neurosurgical Referral Unit

Abstract: Background: Clinically validated guidelines for the management of head injury in children do not exist, and the treatment is often based upon adult management routines. In order to examine the safety of this procedure, an analysis of clinical factors associated with complications after pediatric head injury was attempted. Method: We performed a descriptive retrospective study, including patients who received any S06 diagnosis during treatment in the Neurointensive Care Unit at Lund University Hospital between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…The patient who had a GCS of 13-15 (218) had a poor out come in 8 (3.67%), followed by GCS of 9-12 (92) who had a poor outcome in 22(23.91%) followed be GCS of 8 or less then 8 (35) who had poor outcome in 15(42.86%) which is similar as reported by Astrand R et.al [10].…”
Section: Discussionsupporting
confidence: 84%
“…The patient who had a GCS of 13-15 (218) had a poor out come in 8 (3.67%), followed by GCS of 9-12 (92) who had a poor outcome in 22(23.91%) followed be GCS of 8 or less then 8 (35) who had poor outcome in 15(42.86%) which is similar as reported by Astrand R et.al [10].…”
Section: Discussionsupporting
confidence: 84%
“…The studies in which pediatric forensic cases were evaluated identified the age average as 8,2-9,1 years of age and defined that the frequency of getting injuries increased in preschool age children and school age children. This present study also showed that the age average was similarly 9,2 ± 6,2 and the occurrence of cases was the most frequent in children between 11-17 years of age and preschool children followed [13][14][15]. The fewest of the cases were detected in newborns.…”
Section: Discussionsupporting
confidence: 80%
“…[ 25 ] Astrand et al . [ 26 ] reported poor outcome in GCS 14–15 in 0%, in 9–13 as 6.2%, and < 8 had 22% poor outcome. Ong et al .…”
Section: Discussionmentioning
confidence: 99%
“…Astrand et al . [ 26 ] reported 100% poor outcome in dilated pupils unresponsive to light. Suresh et al .…”
Section: Discussionmentioning
confidence: 99%